Designing a Summer Transition Program for Incoming and Current College Students on the Autism Spectrum: A Participatory Approach - Hotez, Emily; Shane-Simpson, Christina; Obeid, Rita; DeNigris, Danielle; Siller, Michael; Costikas, Corinna; Pickens, Jonathan; Massa, Anthony; Giannola, Michael; D'Onofrio, Joanne; Gillespie-Lynch, Kristen (Frontiers in Psychology, 2018)
Students with Autism Spectrum Disorder (ASD) face unique challenges transitioning from high school to college and receive insufficient support to help them navigate this transition. Through a participatory collaboration with incoming and current autistic college students, we developed, implemented, and evaluated two intensive week-long summer programs to help autistic students transition into and succeed in college. This process included: 1) developing an initial summer transition program curriculum guided by recommendations from autistic college students in our ongoing mentorship program, 2) an initial feasibility assessment of the curriculum (Summer Transition Program 1 [STP1]), 3) revising our initial curriculum, guided by feedback from autistic students, to develop a curriculum manual, and 4) pilot-testing the manualized curriculum through a quasi-experimental pre-test/post-test assessment of a second summer program (Summer Transition Program 2 [STP2]). In STP2, two autistic college students assumed a leadership role and acted as “mentors” and ten incoming and current autistic college students participated in the program as “mentees.” We pilot-tested STP2 using a single group pre-post-test design. Results suggested the benefits of participatory transition programming for fostering self-advocacy and social skills among mentees. Autistic and non-autistic mentors (but not mentees) described practicing advanced forms of self-advocacy, specifically leadership, through their mentorship roles. Autistic and non-autistic mentors also described shared (e.g., empathy) and unique (an intuitive understanding of autism versus an intuitive understanding of social interaction) skills that they contributed to the program. This research provides preliminary support for the feasibility and utility of a participatory approach in which autistic college students are integral to the development and implementation of programming to help less experienced autistic students develop the self-advocacy skills they will need to succeed in college.